Comparative study of production and profitability of strains of Nile tilapia for small scale commercial cage farming - Babe, M.; Agyakwah, S. K.; Amevenku, F. K.; Mensah, E. T-D.; Asmah, Ruby; Ragasa, Catherine; Trong, Q. T. (2022)
The study compared growth performance and economic characteristics of three strains (Akosombo generation 11, Huawei and Fish Reit) of Nile tilapia in cages under small-scale commercial farm management practice. A total of six cages were each stocked at 32 fish/m3 with 4,200 fingerlings at stocking size of 2.00 ± 1.09 g. Water quality parameters were within acceptable limits and readings showed no significant differences between treatments (p > 0.05). After 136 days of culture, the final mean weight for Huawei (393.30 ± 100.70 g) was significantly higher than Fish Reit (204.90 ± 53.15 g) and Akosombo strain (190.50 ± 48.75 g)(p < 0.05). Mean yield for Huawei was significantly higher (10.35 kg/m3) than Akosombo strain (3.16 kg/m3) (p < 0.05) but neither of these two were different from Fish Reit (6.28 kg/m3) (p > 0.05). Economic indicators of performance also revealed that the Huawei strain performed better followed by Fish Reit and ARDEC Akosombo strain in that order. However, the sources of the Huawei and Fish Reit strains are not known with certainty thus making it difficult to be relied upon for the development of stocking materials. The study recommends that challenges related to the development of the local, better known ARDEC Akosombo strain be tackled by researchers and policy makers to address issues of inadequate supply of quality seeds of desirable economic characteristics on sustainable basis.